2017
DOI: 10.1016/j.jped.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment improves urodynamic prognosis in neurogenic voiding dysfunction: 20 years of experience

Abstract: Treatment onset within the first year of life improves urodynamic prognosis in patients with neurogenic bladder and triplicates the probability of urodynamic improvement in two years. The role of neonatologists and pediatricians in early referral is extremely important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Different urodynamic patterns of overactive bladder were observed, but the majority of patients examined presented with reduced bladder capacity and abnormally high detrusor filling pressure, both well established high-risk urodynamic indicators that frequently cause progressive urinary system damage if left untreated [ 15 ][ 16 ]. Of note, it is well documented that the risk for upper urinary tract compromise is related to the length of time that the bladder maintains a high detrusor pressure during the filling phase [ 13 ][ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different urodynamic patterns of overactive bladder were observed, but the majority of patients examined presented with reduced bladder capacity and abnormally high detrusor filling pressure, both well established high-risk urodynamic indicators that frequently cause progressive urinary system damage if left untreated [ 15 ][ 16 ]. Of note, it is well documented that the risk for upper urinary tract compromise is related to the length of time that the bladder maintains a high detrusor pressure during the filling phase [ 13 ][ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…An alternate approach would be to create a clinical control group, based on other neurogenic bladder diagnoses. However, we have noticed that the urological patterns of Zika patients are far too different from other patients with neurogenic bladder that we have followed for the last 25 years [ 15 ] in a way that would make any comparison unrealistic.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 59 eligible patients, only 11 (19%) had their bladders function back to baseline after standard therapy, confirming the need to alternative treatment options for the patients with NB. The use of TENS may be an option for those patients who do not respond well to conventional treatment for NDO, or who present side effects to medications, which leads to low adherence to treatment as shown in previous studies . Patients may benefit by having their bladder pressure reduced, and, consequently, reducing NDO morbidity and improving their quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…Compliance to treatment has been a problem. A recently published review (20 years follow‐up of 230 patients with NB) confirmed that among the 230 patients included, only 49% complied with their regular treatment schedule, and 32% fail to improve risk patterns at the first posttreatment evaluation …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation